TOWARDS A CRITICAL AND REFLECTIVE PLANNER: A CONTRIBUTION TO IMPROVED PRACTICE USING THE CASE STUDY OF THE AVALA FILM COMPLEX - Maruna, Marija; Graovac, Ana (Arhitektura i urbanizam, 2021)
The aim of this paper is to illustrate the results of the pedagogical approach that was created to develop the competencies of a critical and reflective professional. The pedagogical approach was developed for the master’s level Planning Theory course at the Faculty of Architecture, University of Belgrade. The specifics of the pedagogical approach stemmed from the need to consider a number of new issues relevant to improving planning practices, planning systems and the domain of spatial development in Serbia, which have emerged during the period of transitional reforms in Serbia since 2000. The case of preparing the plan of detailed regulation for the Avala Film complex in Kosutnjak, which was also the subject of the work of students in the school year 2020/21, was taken as a testing ground to illustrate the approach. The methodological steps in the analysis of the case clearly indicated the following problems in the field of spatial development: a) urban plans serve as an instrument for the alienation of publicly owned land, b) public policies are selectively considered in the decision-making process on spatial development, c) formal planning procedures are insufficiently clear and have gaps in formulations, which creates space for ambiguous interpretations, d) decision-making positions on strategic development priorities and issues of public interest are not clearly defined and e) key issues on spatial development are resolved in the domain of political rather than professional decision-making. Based on the analysis of the planning process for the Avala Film complex, recommendations for improving planning practice, i.e. the spatial governance system in Serbia are made. They are essentially aimed at improving the legislative system in the decision-making process, with an emphasis on formalizing positions of competence, determining mechanisms for the alienation of public property, improving the transparency of procedures and re-positioning the role of the profession in that process.
Keywords: critical and reflective planner; spatial governance; pedagogical approach; professional competencies; Avala Film complex